Paeoniflorin alleviates sepsis-associated acute kidney injury in mice by inhibiting aerobic glycolysis through the β-catenin/c-Myc pathway - GONG Yu; LEI Jiao; ZHANG Ming (陆军军医大学学报)
Objective‍‍　‍To investigate the role and mechanism of paeoniflorin （PF） in sepsis-associated acute kidney injury （SA-AKI） in mice. Methods‍　‍Mouse SA-AKI model was constructed by intraperitoneal injection of 15 mg/kg LPS. Twenty-four male C57BL/6J mice （6~8 weeks old， weighing 20~25 g） were randomly divided into Control group， model group， PF group （intraperitoneally injected with 50 mg/kg PF 30 min before LPS administration）， and β-catenin specific agonist BML284 group （10 mg/kg BML284 by intraperitoneal injection after 50 mg/kg PF administration）. The renal histopathological changes were observed by HE staining and Paller scoring. ELISA was used to determine the contents of serum creatinine （Scr）， neutrophil gelatinase-associated lipocalin （NGAL） and lactate， and renal contents of hexokinase 2 （HK2）， lactate dehydrogenase A （LDHA）， IL-1β and IL-18. Western blotting was performed to detect the expression of total β-catenin， p-β-cateninY654， nucleus β-catenin and c-Myc. Results‍　‍Compared with the Control group， the LPS group showed obviously damaged renal tissue， higher Paller score （P<0.05）， increased serum Scr and NGAL levels （P<0.05）， elevated renal contents of aerobic glycolytic indexes such as HK2， LDHA and serum lactate， as well as contents of IL-1β and IL-18 （P<0.05）， and enhanced expression of total β-catenin， p-β-cateninY654， nucleus β-catenin and c-Myc in the renal tissue （P<0.05）. PF treatment attenuated the renal tissue damage， decreased Paller score （P<0.05）， reduced serum Scr and NGAL levels （P<0.05）， HK2， LDHA and serum lactate levels， and contents of IL-1β and IL-18 in renal tissues （P<0.05）， and down-regulated the renal expression of total β-catenin， p-β-cateninY654， nucleus β-catenin and c-Myc when compared with the levels in the model group （P<0.05）. While， addition of BML284 reversed above effects of PF treatment with significant differences （P<0.05）. Conclusion‍　‍PF can alleviate SA-AKI， and its mechanism may be through its inhibiting the β-catenin/c-Myc pathway， thus reducing the aerobic glycolysis level and inflammatory response in renal tissue. ［‍